'It's my money': Social class and the perception of remittances among Bangladeshi migrants in Japan. (May 2014) - Mahmud, Hasan
This study recognizes migrants' perception of remittances as shaped by their class position both in the home and destination countries. Following Max Weber's idea that individuals' rationality is produced in their sociocultural context, this ethnographic inquiry among a group of Bangladeshi temporary migrants in Japan demonstrates how their interests interact with the structural opportunities and constraints in developing a distinct perception of remittances as a means towards higher social status. Opportunities to earn higher income motivated middle-class families in Bangladesh to send their sons abroad, who persevered in low-class jobs in Japan. While supporting the families through remitting, these migrants became aware that their future social status would depend primarily on their own career in Bangladesh rather than family background. Hence, they began to perceive remittance as a productive capital to develop their future careers. This article argues that their middle-class social position led these migrants to espouse an individualistic orientation and encouraged them to negotiate with their families regarding remittance utilization to ensure both income and prestige. Thus, it highlights the importance of including the migrants' social position in studying migrants' perception of remittances and the impact of remittances on development in the migrants' home countries.